Etične smernice v logopediji - Žemva, Nada (Rehabilitacija (Ljubljana), 2017)
The American Psychological Association Ethical Principles of Psychologists and Code of Conduct define the following general principles: Beneficence and Nonmaleficence, Fidelity and Responsibility, Integrity, Justice and Respect for People's Rights and Dignity. Psychologists respect and protect civil and human rights and the central importance of freedom of inquiry and expression in research, teaching, and publication. They strive to help the public in developing informed judgments and choices concerning human behavior. Ethics Code provides a common set of principles and standards upon which psychologists build their professional and scientific work regardless of their professional work field (e.g., in organisations, schools, health care or rehabilitation programs). Because of anthropological and cultural aspects, psychologist in Slovenia are particularly concerned about ethical standards in dual relationship matters, the collecting and protecting psychometric data and research.
Keywords: ethical issues; Ethics; etične dileme; logopedija; motnje govora; rehabilitacija; rehabilitation; speech and language therapy; Speech Disorders; vocational rehabilitation